PENERAPAN MODEL PROJECT BASED LEARNING DALAM MENULIS TEKS NEGOSIASI - Ghea Reiva Igusmi Putri; Andiopenta Purba; Rahmawati Rahmawati (Universitas Negeri Makassar, 2023)
This research aims to describe the application of Project Based Learning model in learning to write negotiation texts for E.3 phase students. The approach used in this research is a qualitative approach, a descriptive research type. The research data are in the form of words, phrases, sentences, and paragraphs that describe the application of the Project Based Learning model. The data source for this research is the Indonesian language subject teacher for phase E.3. The results of this study show that the application of the Project Based Learning model in learning to write negotiation texts for phase E.3 students, in the steps of determining projects, designing project plans, preparing schedules, and monitoring the progress of student projects, is carried out according to the syntax of the Project Based Learning model. However, in the step of testing project results, it has not been carried out optimally due to time constraints, so the teacher assesses based on student project results only. Based on the results of the study, it can be concluded that the implementation of the Project Based Learning model in writing negotiation texts of E.3 phase students is overall carried out according to the steps of the Project Based Learning model designed in the teaching module.